Clinical experience of medical students in a developing country - Alam Sher, Malik; Quah, Ban Seng (Taylor & Francis Ltd, 2003)
Objective: \ This paper compares the clinical experience in acute conditions of the undergraduate students of a medical school from a developing country (Malaysia) with those from a developed country (UK). Methods: This study was conducted at the School of Medical Sciences, Universiti Sains Malaysia (USM). Through questionnaire survey enquiry was made about 27 acute medical conditions (i.e. conditions related to internal medicine, paediatrics, and psychiatry), 15 acute surgical conditions (i.e. conditions related to general surgery, orthopaedics, ophthalmology, otorhinolaryngology, gynaecology and obstetrics), 15 surgical operations and 26 practical procedures. The results obtained were compared with published data from the UK. Results: Acute medical conditions were seen by higher number of the USM students but with less frequency than the British students. The USM students saw practical procedures more frequently than the British students did, but almost an equal number performed these procedures independently. The British students attended surgical operations more frequently than the USM students did. Conclusion: Given the limitations of comparison (epidemiological, cultural and geographical differences, conventional curriculum (in the British medical schools) vs. problem based learning curriculum (in the Malaysian medical school)) the overall clinical experience of the medical students in the USM and the UK was comparable. The USM students had more opportunities to observe cases and procedures but ‘‘hands on’’ experience was similar to that of the British students.